Using response surface methods to explore and optimize mating disruption of the leafminer Phyllocnistis citrella (Lepidoptera: Gracillariidae) - Willett, Denis S.; Stelinski, Lukasz L.; Lapointe, Stephen L. (Frontiers in Ecology and Evolution, 2015)
The application of synthetic sex pheromones to disrupt mating of agricultural pests can be an effective and environmentally friendly alternative to pesticide applications. Optimizing mating disruption through examination of multiple interrelated variables may contribute to wider adoption in agriculture, especially in situations where pheromone synthesis is expensive. Simulations and field experiments designed to produce response surfaces by varying the distribution and number of pheromone dispensers suggested procedures whereby understanding optimization might be increased over that resulting from more common experiments focusing on one factor at a time. Monte Carlo simulations of a spatially explicit agent-based model resulted in nonlinear disruption profiles with increasing point source density. Field trials conducted in citrus infested by the leafminer Phyllocnistis citrella varied the amount of pheromone applied at each point source and point source density using attractive and non-attractive disruption blends. Trap catch disruption in the field resulted in nonlinear disruption profiles similar to those observed with simulations. Response surfaces showed an interaction between the amount of pheromone applied and the number of point sources for the attractive blend, but not for the non-attractive blend. Disruption surfaces were combined with cost curves to optimize trap catch disruption under real world cost constraints. The methods used here highlight the importance of experiment design for understanding the underlying biological dynamics governing mating disruption and optimizing its implementation.